Representations of Disability in Qur’anic Narratives - Ali, Akbar (Journal of disability & religion, 2025)
In some Muslim cultures disabled people are ridiculed, abused and face social injustice. Whilst there are texts which examine the representations of disabled people in a range of legal, social, religious, and cultural Muslim documents, there is a paucity of literature which analyzes the representations of disabled people in the Qur’an. Applying critical discourse analysis, this study interprets two well-known Qur’anic stories. Through the application of thematic analysis, the phrases, clauses and sentences of these two stories are analyzed in order to present patterns of meaning which challenge ableism from a scriptural Islamic perspective.